Hubungan Pola Makan Dan Gaya Hidup Dengan Angka Kejadian Hipertensi Pralansia Dan Lansia Di Wilayah Kerja Puskesmas I Kembaran - Widianto, Ajikwa Ari; Romdhoni, Muhammad Fadhol; Karita, Dewi; Purbowati, Mustika Ratnaningsih (Universitas Muhammadiyah Semarang, 2018)
Relationship between diet and lifestyle with the incidence of hypertension in the pre-elderly and the elderly in the working area of Puskesmas I KembaranBackground: Hypertension is also known as The Silent Killer since it is a hidden killer which its prevalence is very high and tends to increase in the future. Besides, its high malignancy affects in the form of permanent disability and sudden death. Primary Health Care Center (Puskesmas ) I Kembaran obtained the second highest occurrence of hypertension reported by the Banyumas Health Office (Dinas Kesehatan Banyumas), consisted of 2287 cases. Many risk factors affect to hypertension, especially diet and lifestyle.Objective: Determine whether there was a correlation between diet and lifestyle to the occurrence of hypertension in pre-elderly and elderly in the working area of Puskesmas 1 Kembaran.Method: Analytic observational with Cross sectional approach and applied simple random sampling technique. This study was conducted by 50 pre-elderly and elderly respondents who participated PROLANIS (Chronic Disease Management Program) at Puskesmas 1 Kembaran. Questionnaire was implemented to measure the diet and lifestyle, while blood pressure was obtained by sphygmomanometer. Data analysis technique conducted was chi square test.Result: Chi square test to determine the correlation between diet and lifestyle to the occurrence of hypertension. The results of the analysis of diet variable obtained p = 0.003 and the lifestyle variable was p = 0.023.Conclusion: There was a correlation between diet and lifestyle to the occurrence of hypertension in pre-elderly and elderly in the working area of Puskesmas 1 Kembaran, where diet and lifestyle are not good trigger s a higher occurance of hypertension.